2019
DOI: 10.3390/polym11081242
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Flame Retardance of Polyisocyanurate Foams by Dibenzo[d,f][1,3,2]dioxaphosphepine 6-Oxide-Containing Additives

Abstract: A series of new flame retardants (FR) based on dibenzo[d,f][1,3,2]dioxaphosphepine 6-oxide (BPPO) incorporating acrylates and benzoquinone were developed previously. In this study, we examine the fire behavior of the new flame retardants in polyisocyanurate (PIR) foams. The foam characteristics, thermal decomposition, and fire behavior are investigated. The fire properties of the foams containing BPPO-based derivatives were found to depend on the chemical structure of the substituents. We also compare our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…All the MCC data are in agreement with the limiting oxygen index (LOI) results obtained from CYs of thermogravimetric analysis (TGA) experiments: LOI = 1.75 + (0.4 × CY), where DOPO-free OPE-2St produced a lower LOI value than DOPO-containing thermosets, and it is noted that a low LOI means high flammability. In general, thermosets prepared from PPO-, OPE-, and PPE-based resins are capable of forming an excess char layer on the top so that the internal flammable liquids of the thermoset are not exposed to the fire quickly. ,, For DOPO-based thermosets, the flame retardancy mechanism was mainly due to the formation of P-containing gases (responsible for capturing the highly active secondary free radicals such as H • and OH • ). , In this work, the flame retardancy mechanism is expected to be due to the DOPO moiety rather than the OPE segment because OPE-2St could not pass the UL-94 test.…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…All the MCC data are in agreement with the limiting oxygen index (LOI) results obtained from CYs of thermogravimetric analysis (TGA) experiments: LOI = 1.75 + (0.4 × CY), where DOPO-free OPE-2St produced a lower LOI value than DOPO-containing thermosets, and it is noted that a low LOI means high flammability. In general, thermosets prepared from PPO-, OPE-, and PPE-based resins are capable of forming an excess char layer on the top so that the internal flammable liquids of the thermoset are not exposed to the fire quickly. ,, For DOPO-based thermosets, the flame retardancy mechanism was mainly due to the formation of P-containing gases (responsible for capturing the highly active secondary free radicals such as H • and OH • ). , In this work, the flame retardancy mechanism is expected to be due to the DOPO moiety rather than the OPE segment because OPE-2St could not pass the UL-94 test.…”
Section: Results and Discussionmentioning
confidence: 90%
“…34,35,41 For DOPObased thermosets, the flame retardancy mechanism was mainly due to the formation of P-containing gases (responsible for capturing the highly active secondary free radicals such as H • and OH • ). 20,42 In this work, the flame retardancy mechanism is expected to be due to the DOPO moiety rather than the OPE segment because OPE-2St could not pass the UL-94 test.…”
Section: Resultsmentioning
confidence: 92%
“…Lorenzetti et al concluded that the lowest phosphorus valence (+1) was active in both the gas and condensed phases, while the highest phosphorus valence (+5) only worked in the condensed phase [88]. Lenz et al compared phosphorous flame retardants with different phosphorus oxidation states (+1, +3, +5) [89]. They observed that the phosphorous flame retardants with the lowest phosphorus valence (+1) were more effective in the gas phase.…”
Section: Flame-retardant Performance Optimization Of Phosphorusmentioning
confidence: 99%
“…Polyurethane (PU) is one of the most versatile polymers and it is used to provide materials with a wide range of chemical, thermal, and mechanical properties. Although many different PU materials are available, further improvement of the physical properties, especially thermal stability and flame retardancy, will make them suitable for an increased number of applications and meet the new market demands. The introduction of polyisocyanaurate (PIR) and phosphorus motifs in polyurethanes can lead to PUs with better thermal properties as polyisocyanaurate is well known to have a high decomposition temperature and phosphorus motifs are usually used as flame retardants in polymers. However, the brittleness of PIR networks and the limited compatibility of phosphorus motifs with the PUs are challenges that need to be improved.…”
Section: Introductionmentioning
confidence: 99%